Comparison between dog-bone and Gaussian specimens for size effect evaluation in gigacycle fatigue (Fracture and Structural Integrity, 2013)
Gigacycle fatigue properties of materials are strongly affected by the specimen risk volume (volumeof material subjected to a stress amplitude larger than the 90% of the maximum stress). Gigacycle fatigue tests,performed with ultrasonic fatigue testing machines, are commonly carried out by using hourglass shapedspecimens with a small risk volume. The adoption of traditional dog-bone specimens allows for increasing therisk volume, even if the increment is quite limited. In order to obtain larger risk volumes, a new specimen shapeis proposed (Gaussian specimen). The dog-bone and the Gaussian specimens are compared through FiniteElement Analyses and the numerical results are validated experimentally by means of strain gagesmeasurements. The range of applicability of the two different specimens in terms of available risk volume andstress concentration effects due to the cross section variation is determined.
Keywords: Ultrasonic testing machine